Numerical simulation of the flow through an aqxial tidal-current turbine employing an elastic-free-surface approach. - Fernando Mattavo de Almeida (2018)
Together with the world economic growth is the increasing of energy generation demand. However, the upgrade of world power production capability could affect the environment negatively. Even the clean and renewable sources, such as hydroelectricity and wind powers have socio-economic and environmental disadvantages. For example, the required flooded area for a hydro power plant construction could devastate entire forests, and the installation of a wind farm power plant could affect migratory rotes of birds and generate high levels of noise. Hence, for the balancing of advantages and disadvantages of each power generation source, it is necessary to diversify, which requires investments in new power sources. In this context, the energy generation in the ocean is highlighted. The first point concerning the ocean energy is that there is no need of population removal from the installation area, such as the onshore based methods and the second point is that most of the population is concentrated in coastal areas. Therefore the production occurs near to the demand, decreasing the costs with energy distribution. The two main methodologies for harassing energy from oceans are based on gravity waves and in tides. And since the tidal cycles are governed mainly by the gravitational interaction between oceans, Moon and Sun, they are easily predictable, which increases the reliability of such systems. These works explores methodologies to analyse the power generation from a single axial tidal current turbine through a Steady State RANS methodology. Are discussed the effects of flow directionality, inlet velocity profile and turbulence levels and the results are compared with an experimental scheme. It is proposed an alternative methodology for free surface modelling in the CFD analysis. The usual methodology, VOF, it is based on a homogeneous, biphasic approach which requires an additional mesh refinement and is computationally expensive. This new methodology introduces an elastic wall approach in the free surface region in which the stiffness is calculated to provide the same restoring effect as gravity. In general, the results for open domain matched with the experimental results, validating the numerical model and the confined domain has shown a higher power and thrust coefficients if compared with the open domain, which is in accordance with the actuator disk theory approach. The elastic free surface presented convergence problems related to high Froude numbers and therefore to high deformations. However, a simulation with 10% of the original inlet velocity was performed, achieving reasonable results for both power and thrust coefficients evaluation.